Effects of multiple element doping in NiTi based SMAs: Variation of phase transition and structural properties with Cu and Ag doping - Tatar, Cengiz; Mohammed, Safar Saeed; Kanca, M. Sait; Qadir, Rezhaw Abdalla; Kok, Mediha (Iop Publishing Ltd, 2025)
In this study, Ni41-2xTi49Cu7+xAg3+x (x = 0, 1, 2, 3) shape memory quaternary alloys were synthesized by arc melting, and their thermal, structural and mechanical properties were extensively investigated. Systemically, investigations have been carried out on the phase transformation behavior, thermodynamic properties, microstructure and oxidation resistance of the alloys with increasing Cu and Ag content. Differential Scanning Calorimetry (DSC) showed the shape memory effects of all alloys at low temperature. The transformation temperatures increased with increasing Cu and Ag concentrations. Thermodynamic analysis showed that Gibbs free energy trends and entropy were attributed to increased thermal stability at higher doping levels. XRD analysis confirmed the presence of martensitic (beta 19, beta 19 ') and intermetallic Ti2(NiCu) phases, and grain refinement was found in higher doped samples. Microhardness measurements showed more homogeneous and stabilized microstructures at increasing doping, while SEM imaging showed that the hardness increased significantly. Thermogravimetric analysis showed that Cu and Ag slightly compromised the oxidation resistance due to the destabilization of the passive oxide layers. These results suggest that varying the Cu and Ag content in NiTi-based alloys is an effective method for improving mechanical strength and thermomechanical performance in advanced engineering applications.
Keywords: NiTi based alloys; multi-element doping; oxidation resistance; phase transformation